EVALUASI PROGRAM PLP STKIP NU INDRAMAYU TAHUN 2023 DENGAN MODEL CIPP - Wahdan Wilsa, Asrizal; Rusilowati, Ani; Cahyono, Edy (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2023)
This study aims to evaluate the implementation of the Pengenalan Lapangan Persekolahan (PLP) program for STKIP Nahdlatul Ulama Indramayu students which consists of 3 study programs namely elementary school teacher education, Indonesian language and literature education, and physical education, health, and recreation using the CIPP model (Context, Input, Process and Product). This qualitative descriptive evaluative research uses data collection techniques in the form of observation, interviews, documentation, and literature review. The results of the study show that 1) The implementation of the PLP program is going well in accordance with the predetermined academic calendar, 2) The PPL organizing organizations carry out their duties according to their respective duties and functions, 3) there are several aspects that need to be improved in implementing the PLP program, 4) vision and goals to produce prospective teachers who have pedagogic, social, personality, and professional competencies have been reflected in the PLP program 5) the results of the PLP practice assessment generally obtained good results.